Probiotic Lactobacterin-Tk2 Therapeutic and Prophylactic Efficiency - Zh.K, Tulemisova; G.T, Kasenova; B, Muzapbarov; R.Zh, Myktybayeva; T.K, Boranbayeva; A.B, Omarova (International Journal of Natural Sciences Research, 2018)
Annotation. The therapeutic and prophylactic efficacy of the “Lactobacterin-TK2” probiotic for correction of clinical and microbiological changes in diarrhea of calves under farming conditions has been studied. The therapeutic efficacy showed that the drug product results in complete recovery. Findings on the calves' productivity showed that animals in the experimental groups grew more intensively than animals in the control group during the drug product administration by calves. Use of “Lactobacterin-TK2” probiotic in the treatment and prevention of gastrointestinal infections in calves has provided 100% therapeutic and preventive efficacy. We believe that the effect has been obtained due to the sanitation of the animals intestines from pathogenic flora by suppressing of pathogenic and conditionally pathogenic bacteria reproduction with lactobacilli as a result of their antagonistic activity and colonization of the intestine freed ecological niche with normal microbial flora, stimulation of humoral and cellular immunity factors, level of nonspecific resistance of the organism, activation of metabolic processes, normalization of intestinal microbiocenosis in calves. All this immediately influenced the improvement of digestion processes, which led to more intensive growth and development of animals.